Red Flags sebagai moderating pengaruh intellectual capital terhadap earnings quality - Giska Hawa Syahrani; R. Rosiyana Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to examine and analyze the effect of intellectual capital on earnings quality with a red flags as a moderating variable. For the methodology this research uses the quantitative method. The data used are secondary data obtained from Indonesia stock Exchange. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. The sample was selected using the purposive sampling method to produce 84 companies with a total observation of 252 research samples. The data analysis technique used in this research is Multiple Linear Regression Analysis. The result of this study indicates that intellectual capital have a positive and significant effect on earnings quality, while red flags have no significant effect on earnings quality, and red flags weaken the effect of intellectual capital on earnings quality.